Atrial Septal Defect with Eisenmenger Syndrome: A Rare Presentation. (9th March 2020) - Forlemu, Arnold Nongmoh; Ajmal, Muhammad; Saririan, Mehrdad
Abstract : Atrial septal defects (ASDs) are common congenital heart defects (CHD). The clinical course in patients without closure of the ASD is associated with significant morbidity and mortality in advanced age. A small percentage of patients may develop pulmonary arterial hypertension (PAH) due to left to right shunting that impacts morbidity and mortality. Advances in prenatal screening and fetal echocardiography have allowed timely interventions. Nonetheless, some patients still may be diagnosed with ASD in adulthood as an incidental finding or presenting with clinical symptoms such as shortness of breath from right heart failure. We report a case of an adult female presenting with shortness of breath due to ASD causing PAH with Eisenmenger physiology.